2014
DOI: 10.1111/jcom.12097
|View full text |Cite
|
Sign up to set email alerts
|

Media Entertainment and Well-Being-Linking Hedonic and Eudaimonic Entertainment Experience to Media-Induced Recovery and Vitality

Abstract: This paper explores the impact of hedonic and eudaimonic entertainment experience on well‐being. We propose that the satisfaction of recovery needs can provide an important link that connects recent 2‐factor models of entertainment with well‐being after media consumption. Using path modeling, relationships between hedonic/eudaimonic entertainment experiences, media‐induced recovery experience, and vitality as a recovery outcome were explored in an experiment (N = 120). Results suggest that different recovery n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
121
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(128 citation statements)
references
References 44 publications
7
121
0
Order By: Relevance
“…A growing body of research has demonstrated that media use can be a highly successful recovery strategy (Reinecke et al, ; Rieger, Reinecke, Frischlich, & Bente, ) and that media users make frequent use of the recovery potential of media entertainment (Reinecke, ). The existing evidence suggests that media use is more than a simple “low‐effort activity” (Sonnentag, , p. 199) but can elicit the full spectrum of recovery experience (Reinecke, ; Reinecke et al, ).…”
Section: Media‐induced Recovery: Media Use As a Self‐regulatory Resourcementioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research has demonstrated that media use can be a highly successful recovery strategy (Reinecke et al, ; Rieger, Reinecke, Frischlich, & Bente, ) and that media users make frequent use of the recovery potential of media entertainment (Reinecke, ). The existing evidence suggests that media use is more than a simple “low‐effort activity” (Sonnentag, , p. 199) but can elicit the full spectrum of recovery experience (Reinecke, ; Reinecke et al, ).…”
Section: Media‐induced Recovery: Media Use As a Self‐regulatory Resourcementioning
confidence: 99%
“…The existing evidence suggests that media use is more than a simple “low‐effort activity” (Sonnentag, , p. 199) but can elicit the full spectrum of recovery experience (Reinecke, ; Reinecke et al, ). Furthermore, the effects of media‐induced recovery go beyond subjective recovery experience and have consistently been linked to other recovery outcomes, such as increased vitality and cognitive performance (Reinecke et al, ; Rieger et al, ).…”
Section: Media‐induced Recovery: Media Use As a Self‐regulatory Resourcementioning
confidence: 99%
“…The use of entertaining media formats helps to recover from stressful situations experienced in daily life (Reinecke, 2009;Reinecke, Klatt, & Krämer, 2011). Recent research established strong relationships between the use of certain media types and the positive outcomes for mental well-being (Rieger, Reinecke, Frischlich, & Bente, 2014). This well-being has two aspects consists of two components: hedonia and eudaimonia (see Deci EFFECTS OF NEWS CONSUMPTION ON MENTAL WELL-BEING 3 & Ryan, 2008).…”
Section: Disclaimer/complaints Regulationsmentioning
confidence: 99%
“…Hedonic experiences mainly relate to boosting a positive affect, minimizing negative affect and evoking pleasure, whereas eudaimonic experiences, are mainly about satisfaction with life and goals of self-acceptance, personal growth, relatedness and mastery (Deci & Ryan, 2008). The current study focuses on the first component -hedonic experienceswhich offer positivity and psychological detachment, and thereby contribute to vitality and increased mental well-being of citizens.Though positive effects of entertainment have been found (Rieger et al, 2014), how citizens' mental well-being may be affected by the consumption of news programs is still unknown. News is a genre pivotal in the media effects literature, but mostly related to political outcome variables.…”
mentioning
confidence: 99%
See 1 more Smart Citation